As mudanças climáticas e o impacto na operação das empresas - Bristot, Diogo Trucolo (My University, 2026)
The general objective of this study is to identify the impacts that climate change may have on business operations. The specific objectives are: to conduct a literature review on climate changes that have occurred in Rio Grande do Sul over the past 10 years; to conduct a literature review on potential climate changes likely to occur in Rio Grande do Sul over the next 10 years; to identify "through the literature" positive and negative impacts of climate change on business operations in Rio Grande do Sul over the past decade; to identify"through the literature" positive and negative impacts that climate change may bring to business operations in Rio Grande do Sul over the coming decade; and to formulate recommendations for companies regarding climate-related strategies that can be implemented to improve operational performance and mitigate the negative effects of climate change. The study employs a qualitative approach and an exploratory level, utilizing documentary and bibliographic research strategies; data collection involved gathering secondary data and analyzing documents and texts, while data analysis was conducted using content analysis. The results obtained through documentary research enabled the identification and analysis of information regarding climate change in Rio Grande do Sul over the past 10 years, as well as projections for the coming decade. It was possible to gather data on both observed and potential impacts across social and economic sectors, particularly regarding businesses. Furthermore, the research highlighted negative effects -such as natural disasters and production losses?alongside opportunities, including adaptation, reconstruction, and investments in renewable energy. These results provide a basis for understanding business vulnerability and resilience in the face of climate change within the state. [resumo fornecido pelo autor]
Este estudo tem como objetivo geral: "Identificar os impactos que as mudanças climáticas podem acarretar na operação das empresas". Os objetivos específicos são: Efetuar levantamento bibliográfico sobre as mudanças climáticas que aconteceram nos últimos 10 anos no Rio Grande do Sul; Efetuar levantamento bibliográfico sobre as possíveis mudanças climáticas que podem ocorrer nos próximos 10 anos no Rio Grande do Sul; Buscar na bibliografia impactos positivos e negativos que as mudanças climáticas acarretaram na operação das empresas nos últimos 10 anos no Rio Grande do Sul; Buscar na bibliografia impactos positivos e negativos que as mudanças climáticas podem trazer para a operação das empresas nos próximos 10 anos no Rio Grande do Sul; Criar recomendações às empresas sobre estratégias voltadas às mudanças climáticas que podem ser aplicadas com o objetivo de melhorias em termos de desempenho operacional e também, mitigar os efeitos negativos das alterações climáticas. A metodologia do estudo é de natureza qualitativa, nível exploratório, estratégia de pesquisa documental e bibliográfica, processo de coleta de dados através de levantamento de dados secundários, análise de documentos e textos. A análise de dados através de análise de conteúdo. Os resultados obtidos com a aplicação da pesquisa documental permitiram identificar e analisar informações sobre mudanças climáticas no Rio Grande do Sul nos últimos 10 anos. Também projeções para a próxima década. Foi possível levantar dados sobre impactos observados e potenciais nos setores sociais e econômicos especialmente nas empresas. Além disso a pesquisa destacou efeitos negativos como desastres naturais e perdas produtivas e oportunidades como adaptação, reconstrução e investimentos em energias renováveis. Esses resultados fornecem subsídios para compreender a vulnerabilidade e a resiliência dos negócios frente às mudanças climáticas no estado. [resumo fornecido pelo autor]
Keywords: Mudanças climáticas; Administração de empresas